Unidirectional freeze–thaw redistributes water and amplifies soil microbial heterogeneity in a mecrocosm experiment - Huimin Liu; Yaxian Hu; Yuan Song; Xianwen Li; Xiaorong Wei (Geoderma)
Seasonal freeze–thaw profoundly perturbs soil water and carbon cycling in the mid to high-latitude regions. However, it remains largely unknown how the unidirectional freeze–thaw induced heterogeneity in cryosuction, water migration and redistribution affect layer-specific soil biochemical properties. In this study, a refilled Mollisol was frozen, thawed and peeled into six layers, all-round from outer layer (L1) to inner core (L6) to simulate unidirectional freeze–thaw. We observed that cryosuction drove the soil water to migrate from the inner to outer layers, significantly enriching the water content in the outer layer L1 by ratios of 1.08 ∼ 1.48, but noticeably depleting that in the inner core L6 by ratios of 0.74 ∼ 0.93. Such unidirectional freeze–thaw induced soil water redistribution tended to alleviate the dryness in the L1 of the low moisture columns initially with 30% of water holding capacity (WHC), but rendered the L1 of the high moisture columns (initially with 80% WHC) more susceptible to intensive mechanical destruction during ice crystallization. On the contrary, the water depletion in the inner layer L6 appeared to introduce secondary dry stress to the low moisture columns, but helped to temper the destructive ice expansion in the L6 of the high moisture columns. As a consequence, the soil microbial biomass carbon (SMBC) and CO2 emission rates were significantly higher in the outer layers of the low moisture columns, but noticeable greater in the inner layers of the high moisture columns. After 15 days of recovery from freeze-thaw, the soil respiratory entropy significantly reduced, and the correlation of SMBC and CO2 emission rates with the soil water content evolved from a quadratic to linear function. Although not directly applicable to larger scales, the heterogeneity of soil water and freezing intensity amplified by unidirectional freezing, and the legacy effects on soil microbial communities and respiratory activities observed from this mecrocosm experiment, collectively highlight the necessity to distinguish the unequal responses of different soil layers to the increasingly frequent freeze–thaw cycles under feature climate conditions.